Ethical conflicts in COVID-19 times - Gilberto Vizcaino; José Gilberto Esparza (Journal of Infection in Developing Countries)
The COVID-19 pandemic has created new challenges on multiple fronts including a few ethical concerns. Timely and appropriate access to health services and the need to protect vulnerable people are some of them. An important aspect to consider, at the global level, is the frailty of health systems in many developing countries and the constant threat of these collapsing due to shortage of resources and medical supply. Special attention should be placed towards protecting the health of care workers who are highly exposed to SARS-CoV-2 infection. Research and clinical trials involving COVID-19 patients and healthy human volunteers must be done in strict adherence to the fundamental principles of bioethics, even if finding a solution is an urgent need. Shared responsibility must be assumed as we collectively face a common problem and ethical conflicts must be resolved using, as reference, the guidelines developed by the World Health Organization and other relevant international and national organizations. This would allow responsible action in the face of the pandemic without harming human rights, the individual and collective well-being.